Comparison of Physical Characteristics, Strength and Power Performance Between Elite 3 × 3 and 5 × 5 Male Basketball Players - Mladen Mikić; Milan Isakov; Nikola Andrić; Alen Ninkov; Aleksandar Karać; Tatjana Jezdimirović Stojanović; Marko D. M. Stojanović (Sports)
Background/Objectives: The aim of this study was to explore the differences in physical characteristics, leg strength, and jumping performance between 3 × 3 and 5 × 5 male basketball players. Methods: Twelve elite-level 5 × 5 basketball players (26.0 ± 13.0 years; 201.4 ± 6.6 cm; 95.50 ± 11.50 kg) and twelve elite-level 3 × 3 basketball players (26.7 ± 7.3 years; 193.0 ± 5.1 cm; 98.03 ± 9.77 kg), all male, were enrolled in the study. After anthropometric measurements and standardized warm ups, countermovement jump (CMJ), drop jump (DJ) and isokinetic strength testing were conducted, respectively. Results: An independent two-sample t-test revealed that 5 × 5 athletes were notably (p < 0.005) taller, with a lower body fat percentage (11.9 ± 3.6% vs. 18.6 ± 10.9%) and higher quadricep strength (317.21 ± 36.54 N·m vs. 284.76 ± 29.77 N·m and 313.32 ± 24.08 N·m vs. 285.87 ± 31.2 N·m for left and right leg, respectively). Conversely, 3 × 3 players displayed superior CMJ performance in concentric and eccentric peak forces, peak power, and reactive strength index. In the DJ, 3 × 3 players also excelled in eccentric peak force, reactive strength index, and jump height. Conclusions: The findings indicate that while 5 × 5 basketball players excel in body physique and in the strength of their lower body, 3 × 3 basketball players outperform them in power-related metrics.